Assisted Walking Program on Walking Ability in In‐Hospital Geriatric Patients: A Randomized Trial. Issue 3 (12th November 2020) - Gazineo, Domenica; Godino, Lea; Decaro, Roberta; Calogero, Pietro; Pinto, Daniela; Chiari, Paolo; Zoli, Marco; Ambrosi, Elisa
Abstract : Objectives: The main aim of this study was to evaluate if an individualized assisted walking program (IAWP) for hospitalized older patients could improve walking ability compared with usual geriatric care and rehabilitation. Design: A randomized controlled trial with an active control group, open labeled with parallel assignment was conducted between October 2018 and January 2020. Setting: Geriatric ward. Participants: A total of 387 hospitalized patients (≥65 years) were randomly assigned to an intervention or control (usual‐care) group. Intervention: The control group received usual hospital care. The intervention group received also an IAWP. Measurements: The primary endpoint was change in walking ability from hospital admission (considering both current and pre‐admission status) to discharge, as assessed with the Braden Activity subscale measures. The secondary endpoint was the occurrence of in‐hospital adverse events, such as complications of mobility, pressure ulcers, falls, pain and mortality, and the length of hospital stay. Intention‐to‐treat and per‐protocol analyses were performed. Results: Baseline characteristics were similar between intervention and control groups. The intervention group, relative to the control group, had significantly improved walking ability at discharge ( P < .001). There were no statistically significant differences between the groups in terms of in‐hospital adverse events. No adverse effects were detected. Conclusion: In in‐hospital patients aged 65 and older, an IAWP improves walking ability at discharge.